Development of Project-Based E-Instruments Assisted by Digital Learning Platforms to Enhance Student Creativity in Indonesian Language Lessons - Eri Suryaningsih; Sri Lastuti; Nurul Fauziah (FKIP - Universitas Riau, 2026)
The creativity crisis among elementary school students, especially in the upper grades, has become a serious problem in education. If not addressed immediately, this problem can hamper students' competitiveness before they fully develop their potential. Creativity refers to the ability to generate new ideas and find solutions to any problem. However, many students still struggle with decision-making and innovation. Departing from this problem, this study aims to develop an e-based instrument to enhance student creativity. This e-instrument integrates various learning supports, including teaching modules, worksheets, creativity assessment instruments, and interactive quizzes. This instrument is designed according to the syntax of the Project-Based Learning (PjBL) model and aligns with creativity indicators, enabling students to complete projects without relying on stationery. This study uses the Research and Development (R&D) method with the Nieveen model, which consists of preliminary research, prototyping, summative evaluation, and Systematic Reflection and Documentation Stage. The results show that the e-instrument achieves a high level of validity with an average score of 0.80 (valid category). Its practicality reached 93.41% from teachers and 81.39% from students (both very practical). The N-gain score was 0.61 (moderate). Therefore, the developed E-instrument is valid, practical, and effective in improving student creativity.